Quality characteristics of bread produced from wheat, rice and maize flours - Rai, Sweta (Springer-Verlag, 2011)
Rice (Oryza sativa) flour and maize (Zea mays) meal substitution in wheat (Triticum aestivum) flour, from 0 to 100% each, for the production of bread was investigated. The proximate analysis, pasting properties, bread making qualities of raw materials and sensory evaluation of the bread samples were determined. The pasting temperature increased with increased percentage of rice flour and maize meal. But the other pasting characters decreased with the higher proportion of rice flour. The baking absorption was observed to increase with higher level of maize meal but it decreased when level of rice flour was increased. Loaf weight (g) decreased with progressive increase in the proportion of maize meal but increased when rice flour incorporation was increased. Loaf volume, loaf height and specific volume decreased for progressively higher level of maize meal and rice flour. The sensory evaluation revealed that 25% replacement of wheat flour was found to be more acceptable than control sample.